Functionalization of polymer powders for SLS-processes using an atmospheric plasma jet in a fluidized bed reactor - Sachs, Marius; Schmitt, Adeliene; Schmidt, Jochen; Peukert, Wolfgang; Wirth, Karl-Ernst (AIP Conference Proceedings 1664, 2015)
Recently additive manufacturing processes such as selective laser sintering (SLS) of polymers have gained more importance for industrial applications [1]. Tailor-made modification of polymers is essential in order to make these processesmore efficient and to cover the industrial demands. The so far used polymer materials show weak performance regarding the mechanical stability of processed parts. To overcome this limitation, a new route to functionalize the surface of commerciallyavailable polymer particles (PA12; PE-HD; PP) using an atmospheric plasma jet in combination with a fluidized bed reactor has been investigated. Consequently, an improvement of adhesion and wettability [2] of the polymer surface without restraining the bulk properties of the powder is achieved. The atmospheric plasma jet process can provide reactive species at moderate temperatures which are suitable for polymer material. The functionalization of the polymer powders improves the quality of the devices build in a SLS-proces
Keywords: Atmospheric Plasma Jet; Polymer Functionalization; Fluidized Bed Reactor; SLS-Process